Tributaç\~ao e inovaç\~ao: Uma revis\~ao da literatura - Fernanda De Negri (Instituto de Pesquisa Econômica Aplicada (IPEA), 2022)
The tax reform debate in Brazilian academic and political circles addresses numerous problems in our tax system, aiming to simplify it, increase its efficiency and its progressivity in order to guarantee the State's ability to provide essential public services. A relevant dimension, however, is still not properly addressed by this debate: to what extent can the tax structure induce or hinder innovation, the generation of new businesses and the dynamism of the national productive sector? This text seeks to incorporate this dimension into an already complex and nuanced debate. To this end, it presents a non-systematic review of the international empirical literature on the effects of taxation on investments in Research and Development (R&D) and innovation, in its various aspects. The studies presented deal, among other topics, with the impact of taxes on investment in R&D and in risky assets and on entrepreneurship, as well as how the tax structure can affect relative prices and thus encourage the adoption and diffusion of new technologies, such as environmental ones. Finally, the text analyzes the relevance of tax incentives for R&D.
Keywords: H20; H23; H25; O31; 330; taxation; innovation; tax reform